2016
DOI: 10.1021/acs.est.6b00678
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Neonicotinoids in Honey Bees (Apis mellifera)

Abstract: Neonicotinoids are implicated in the decline of bee populations. As agonists of nicotinic acetylcholine receptors, they disturb acetylcholine receptor signaling leading to neurotoxicity. Several behavioral studies showed the link between neonicotinoid exposure and adverse effects on foraging activity and reproduction. However, molecular effects underlying these effects are poorly understood. Here we elucidated molecular effects at environmental realistic levels of three neonicotinoids and nicotine, and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 72 publications
(135 reference statements)
11
108
4
5
Order By: Relevance
“…To understand how neonicotinoids affect behavior and immunity at the molecular level, Christen et al (2016) looked at transcriptional regulation of 8 genes in caged honeybees fed with field-realistic concentrations of acetamiprid, clothianidin, imidacloprid, and thiamethoxam. They found downregulation of transcription of two genes involved in memory and increased transcription of the gene responsible for vitellogenin, the latter possibly affecting foraging behavior.…”
Section: Experimental (In Vitro) Studiesmentioning
confidence: 99%
“…To understand how neonicotinoids affect behavior and immunity at the molecular level, Christen et al (2016) looked at transcriptional regulation of 8 genes in caged honeybees fed with field-realistic concentrations of acetamiprid, clothianidin, imidacloprid, and thiamethoxam. They found downregulation of transcription of two genes involved in memory and increased transcription of the gene responsible for vitellogenin, the latter possibly affecting foraging behavior.…”
Section: Experimental (In Vitro) Studiesmentioning
confidence: 99%
“…Christen et al (2016) observed that clothianidin, imidacloprid, thiamethoxam, and acetamiprid led to expressional changes of immune system-related genes in honeybees at environmental realistic concentrations. The investigations covered the single compounds as well as their binary mixtures (Christen et al 2016).…”
Section: Invertebratesmentioning
confidence: 95%
“…Further, inhibition of nAChR activity from desensitization can lead to an up-regulation in nAChR expression, termed pharmacological chaperoning (Srinivasan et al, 2012;Flores et al, 1992;Marszalec et al, 2005). Exposure to imidacloprid and thiamethoxam for 72 or 48 h, respectively was shown to significantly increase transcriptional abundance of nAChRα1 subunit in the honey bee brain (Christen et al, 2016). In the desensitized state, nAChR receptors have high affinity for the agonist and therefore establish a blockade to subsequent agonist binding (Ochoa et al, 1989).…”
Section: Normal Biologymentioning
confidence: 99%
“…Closure of the receptor, due to prolonged desensitization is likely to impede Ca 2+ signaling across the nAChR and, hence, downstream components of the pathway, although studies specifically evaluating such desensitization and impacts on Ca 2+ signaling in the insect neuron are lacking. However, Christen et al (2016) evaluated PKA and CREB gene expression in the brain after oral exposure of honey bees to neonicotinoids. Protein kinase A transcripts were significantly decreased after 72 h of exposure to 3 ng imidacloprid/bee and after 48 h of exposure to 0.3 ng clothianidin/bee (Christen et al, 2016).…”
Section: Consideration Of Biological Plausibility and Empirical Supportmentioning
confidence: 99%
See 1 more Smart Citation